Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3389/fpls.2016.00648
|View full text |Cite
|
Sign up to set email alerts
|

Strain of Synechocystis PCC 6803 with Aberrant Assembly of Photosystem II Contains Tandem Duplication of a Large Chromosomal Region

Abstract: Cyanobacterium Synechocystis PCC 6803 represents a favored model organism for photosynthetic studies. Its easy transformability allowed construction of a vast number of Synechocystis mutants including many photosynthetically incompetent ones. However, it became clear that there is already a spectrum of Synechocystis “wild-type” substrains with apparently different phenotypes. Here, we analyzed organization of photosynthetic membrane complexes in a standard motile Pasteur collection strain termed PCC and two no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…The Synechocystis sp PCC 6803 glucose-tolerant substrain GT-P was used as the wild type (Tichý et al, 2016). The DrubA strain was constructed by replacing the slr2033 gene (36-339 bp) by a zeocin antibiotic resistance cassette.…”
Section: Construction and Cultivation Of Strainsmentioning
confidence: 99%
“…The Synechocystis sp PCC 6803 glucose-tolerant substrain GT-P was used as the wild type (Tichý et al, 2016). The DrubA strain was constructed by replacing the slr2033 gene (36-339 bp) by a zeocin antibiotic resistance cassette.…”
Section: Construction and Cultivation Of Strainsmentioning
confidence: 99%
“…Since this disagreement could be caused by differences in the genetic backgrounds of the two WT strains used to make the mutants, we constructed two new Psb28-1-and Psb28-2-less mutants using a different WT strain. In our original study (Dobá ková et al, 2009), we used a WT strain very similar to the glucose-tolerant GT-O2 strain (Morris et al, 2014), which was subsequently shown to exhibit partial Chl depletion upon autotrophic growth conditions (GT-W; Tichý et al, 2016). The new set of mutants was instead constructed in the GT-P strain similar to the GT-Kazusa strain (Supplemental Figure 6), which contains a similar content of Chl as the standard motile PCC 6803 strain (Tichý et al, 2016).…”
Section: Differences In the Profile Of Psii Complexes In Psb28 Null Mmentioning
confidence: 99%
“…In our original study (Dobá ková et al, 2009), we used a WT strain very similar to the glucose-tolerant GT-O2 strain (Morris et al, 2014), which was subsequently shown to exhibit partial Chl depletion upon autotrophic growth conditions (GT-W; Tichý et al, 2016). The new set of mutants was instead constructed in the GT-P strain similar to the GT-Kazusa strain (Supplemental Figure 6), which contains a similar content of Chl as the standard motile PCC 6803 strain (Tichý et al, 2016). The resulting psb28 mutants were found to have a similar cellular Chl content as the control and contained very similar levels of PSI and both monomeric and dimeric PSII core complexes as revealed by CN gel electrophoresis ( Figure 6) in agreement with Sakata et al (2013).…”
Section: Differences In the Profile Of Psii Complexes In Psb28 Null Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Synechocystis sp. PCC 6803 (hereafter Synechocystis) is widely used as a model cyanobacterium for fundamental and applied research because it is naturally transformable (Grigorieva and Shestakov, 1982;Kufryk et al, 2002), can grow heterotrophically on glucose (Anderson and McIntosh, 1991), and has a publicly available genome sequence (Ikeuchi, 1996;Morris et al, 2014;Tichý et al, 2016). Exogenous DNA molecules introduced into Synechocystis via natural transformation may replicate independently on a suitable plasmid (Mermet-Bouvier et al, 1993) or be incorporated into the genome via double homologous recombination (Grigorieva and Shestakov, 1982;Shestakov et al, 1985).…”
Section: Introductionmentioning
confidence: 99%